Terrorism and Conflict-Related Sexual Violence in Africa: Northeastern Nigeria in Focus - & Adejoh Sunday, Nanna Lord-Mallam (Covenant University Journal of Politics and International Affairs, 2018)
The emergence of Boko Haram terrorist organization and its subsequent activities in Nigeria posed egregious security challenges not only to Nigeria but several other countries within Sub-Saharan Africa especially Cameroon, Chad and Niger which are contiguous to Nigeria. The conflict oriented and violent nature of Boko Haram became manifest in 2009 and from then, Nigeria has been battling with this security threat and challenges precipitated by Boko Haram. Terrorism and conflicts are usually characterized with wanton loss of lives and properties,sexual violations and abuses (SEA), refugee’s crisis, Internally Displayed Persons and other forms of humanitarian crisis. It is based on the foregoing that this work attempts to investigate and interrogate the relationships between Boko Haram terrorism and conflict-related sexual violence/exploitation in North Eastern Nigeria with a view to examining and ascertaining the factors that propelled this phenomenon. It is the position of this paper that rape, sexual slavery, forced prostitution, forced pregnancy, forced abortion, enforced sterilization, forced marriage, and any other form of sexual violence used by Boko Haram is a violation of Human Rights. The paper further argued that Boko Haram conflict related-sexual violence/exploitation is not only perpetuated by Boko Haram as the Military, Police, Civilian JTF and some staff of NGOs are also perpetuators. Women are sexually violated by soldiers in the process of countering terrorism. Sex is offered in exchange for protection and relief materials. This research relied on secondary materials and Robert K Merton’s theory of Anomie as tool for analysis. In the final analysis it recommends among others the need to include sexual violence in Nigeria’s Terrorism Prevention (Amendment) Act, 2013, so as to criminalize rapewhich furthers the ends of terrorist groups.